Mineralogy and pore topology analysis during matrix acidizing of tight sandstone and dolomite formations using chelating agents - Shafiq, M.; Ben Mahmud, Hisham; Arif, M. (Elsevier, 2018)
© 2018 Hydrochloric acid (HCl) is commonly used during acidizing but certain problems are associated with its application such as corrosion of pipes, environment hazards, precipitation of fluosilicates or calcium fluorides and incompatibility of HCl with clay minerals. In order to mitigate these problems, few studies have proposed the use of chelating agents (the chemical compound that reacts with metal ions to form stable, water-soluble metal complexes) as an alternative. In this study, three different chelating agents, Ethylenediaminetetraacetic Acid (EDTA), N-(2-Hydroxyethyl) ethylenediamine-N,N',N'-triacetic Acid (HEDTA) and N-Acetyl-L-glutamic Acid (GLDA) were used to stimulate Colton tight sandstone and Guelph dolomite samples. The pH value of these chelates ranged from 1.7 to 3 and was measured before and after the core flooding to observe the physicochemical changes in rock/fluid mixtures. Core flood experiments under 180 °F temperature were conducted on core samples at slow injection rate which increased the contact time between the fluid and the rock and increased the amount of dissolved ions. Porosity, permeability, Inductively Coupled Plasma (ICP), and Tescan Integrated Mineral Analysis (TIMA) were employed to measure the changes in the formation properties. The effluent samples were analyzed for calcium, magnesium, aluminium, sodium, potassium, silicon and iron using the ICP to assess the ability of these chelates on the complexation of these ions. HEDTA showed a strong ability in chelating calcium, iron, magnesium, sodium and it chelated small amounts of aluminium ions from the sandstone cores. Porosity distribution analysis showed that the HEDTA was more effective in creating fresh pore spaces in sandstone formation while GLDA introduced a large amount of pore spaces in the dolomite. A large number of solid particles were dissolved using HEDTA in sandstone and GLDA in dolomite formations. Panorama of each sample shows that new wormholes had been created by all chelates. The research introduced the chelates application in sandstone and dolomite formations and they showed good results in terms of matrix acidizing. Moreover, the Tescan Integrated Mineral Analysis (TIMA) has not been applied before to test the change in pore structure and mineralogy during the acidizing.